Dielectrophoretic analysis of treated cancer cells for rapid assessment of treatment efficacy. Issue 8 (23rd February 2018) - Mahabadi, Sina; Labeed, Fatima H.; Hughes, Michael P.
Abstract: Whilst personalized medicine (where interventions are precisely tailored to a patient's genotype and phenotype, as well as the nature and state of the disease) is regarded as an optimal form of treatment, the time and cost associated with it means it remains inaccessible to the greater public. A simpler alternative, stratified medicine, identifies groups of patients who are likely to respond to a given treatment. This allows appropriate treatments to be selected at the start of therapy, avoiding the common "trial and error" approach of replacing a therapy only once it is demonstrated to be ineffective in the patient. For stratification to be effective, tests are required that rapidly predict treatment effectiveness. Most tests use genetic analysis to identify drug targets, but these can be expensive and may not detect changes in the phenotype that affect drug sensitivity. An alternative method is to assess the whole‐cell phenotype by evaluating drug response using cells from a biopsy. We assessed dielectrophoresis to assess drug efficacy on short timescales and at low cost. To explore the principle of assessing drug efficacy we examined two cell lines (one expressing EGFR, one not) with the drug Iressa. We then further explored the sensitive cells using combinations of chemotherapeutic and radiotherapeutic therapies. Our results compare with known effects of these cell/treatment combination, and offer the additional benefit over methods such as TUNEL of detecting drug effects such as cell cycle arrest, which do not cause cell death.